Biomarkers for rheumatoid arthritis associated lung disease - Oka, Shomi; Tohma, Shigeto; Furukawa, Hiroshi (Clinical Rheumatology and Related Research, 2020)
Interstitial lung disease（ILD）and airway disease（AD）are frequently associated with rheumatoid arthritis（RA）patients. Lung diseases including ILD and AD in RA are extra-articular manifestations. Since ILD and AD cause a poor prognosis in RA, biomarkers for lung diseases in RA were eagerly desired. Acute exacerbation of ILD, drug-induced ILD, and Pneumocystis pneumonia occasionally occur in RA, and are included in acute-onset diffuse ILD（AoDILD）. AoDILD in RA causes poor prognosis.Krebs von den lungen-6（KL-6）and surfactant protein-D（SP-D）were originally generated for biomarkers of idiopathic pulmonary fibrosis and the sensitivity of these markers were lower for RA patients with ILD. However, few biomarker studies on ILD, AD, or AoDILD in RA have been reported to date. Thus, we have been trying to generate biomarkers for RA patients with lung diseases. Genome, cytokine, amino acid, antibody, micro RNA, and metabolomic profiles of lung diseases in RA were investigated in order to generate better potential biomarkers. In this review, we have attempted to summarize the investigated biomarkers for RA patients with lung diseases.